Helicobacter pylori genetic diversification in the Mongolian gerbil model - Beckett, Amber C.; Loh, John T.; Chopra, Abha; Leary, Shay; Lin, Aung Soe; McDonnell, Wyatt J.; Dixon, Beverly R.E.A.; Noto, Jennifer M.; Israel, Dawn A.; Peek Jr, Richard M.; Mallal, Simon; Algood, Holly M. Scott; et al. (PeerJ, 2018)
Helicobacter pylori requires genetic agility to infect new hosts and establish long-term colonization of changing gastric environments. In this study, we analyzed H. pylori genetic adaptation in the Mongolian gerbil model. This model is of particular interest because H. pylori-infected gerbils develop a high level of gastric inflammation and often develop gastric adenocarcinoma or gastric ulceration. We analyzed the whole genome sequences of H. pylori strains cultured from experimentally infected gerbils, in comparison to the genome sequence of the input strain. The mean annualized single nucleotide polymorphism (SNP) rate per site was 1.5e−5, which is similar to the rates detected previously in H. pylori-infected humans. Many of the mutations occurred within or upstream of genes associated with iron-related functions (fur, tonB1, fecA2, fecA3, and frpB3) or encoding outer membrane proteins (alpA, oipA, fecA2, fecA3, frpB3 and cagY). Most of the SNPs within coding regions (86%) were non-synonymous mutations. Several deletion or insertion mutations led to disruption of open reading frames, suggesting that the corresponding gene products are not required or are deleterious during chronic H. pylori colonization of the gerbil stomach. Five variants (three SNPs and two deletions) were detected in isolates from multiple animals, which suggests that these mutations conferred a selective advantage. One of the mutations (FurR88H) detected in isolates from multiple animals was previously shown to confer increased resistance to oxidative stress, and we now show that this SNP also confers a survival advantage when H. pylori is co-cultured with neutrophils. Collectively, these analyses allow the identification of mutations that are positively selected during H. pylori colonization of the gerbil model.
Keywords: Helicobacter pylori; Quasispecies; Mutation; Genetic diversity; Evolution; Animal models